Long-term snow-track indices of a Finnish native mesopredator declined while those of an invasive one increased - Selonen, Vesa; Toivonen, Pyry; Lindén, Andreas (Springer Science and Business Media LLC, 2025)
Monitoring both native and invasive species is crucial for understanding their ecological impacts. However, obtaining reliable data can be challenging, especially for elusive species like mesopredators. This study utilized snow-track surveys in Finland (1989-2022) to examine population trends of the invasive raccoon dog and the native red fox. While raccoon dogs are known to reduce activity during cold weather, we demonstrated that accounting for temperature and snowfall allows for effective population trend estimation using snow-track data. Track accumulation decreased in cold and snowy weather more clearly for raccoon dogs than for red foxes. We also found that the track accumulation of the raccoon dog had significantly increased, while those of the red fox population had declined, particularly in southern parts of the country. Notably, raccoon dog snow-track numbers increased in northern regions, suggesting a potential for further range expansion under a warming climate. These findings reveal a concerning shift in Finland's mesopredators abundance due to the invasive species' success and the decline of the native species. Thus, the invasive raccoon dog is likely to have an increasing role in those northern ecosystems where it interacts with the native fauna.